The regulation of microglia by aging and autophagy in multiple sclerosis - Xiying Wang; Ye Sun; Haojun Yu; Chunran Xue; Xuzhong Pei; Yi Chen; Yangtai Guan (Pharmacological Research)
Multiple sclerosis (MS) is an inflammatory disease that is often characterized by the development of irreversible clinical disability. Age is a strong risk factor that is strongly associated with the clinical course and progression of MS. Several lines of evidence suggest that with aging, microglia have an aging-related gene expression signature and are close to disease-associated microglia (DAM), which exhibit decreased phagocytosis but increased production of inflammatory factors. The gene expression signatures of microglia in MS overlap with those in aging, inflammation and DAM. Moreover, the clearance of damaged myelin by microglia is impaired in the aged brain. Autophagy is a cellular process that decreases in activity with age. In this review, we provide an overview of the role of autophagy and aging in MS. We describe the impact of autophagy and aging on microglial activation in MS and the molecules involved in autophagy and aging, which are related to the phagocytosis and activation of microglia. We propose that a decrease in autophagy in microglia occurs with aging, leading to a decrease in phagocytosis. Decreases in phagocytosis and increases in the production of inflammatory factors by microglia contribute to chronic inflammation in the aged brain and disease progression in MS. Thus, the modulation of autophagy in microglia serves as a potential therapeutic target for MS.